Mechanism of Oxidation of L-Cysteine by Tetraoxoiodate(VII) in Aqueous Acid Medium - O. Ukoha, Pius; T. Ujam, Oguejiofo; F. Iyun, Johnson; E.O. Okereke, Solomon (Asian Journal of Chemistry, 2015)
The kinetics and mechanism of the oxidation of L-cysteine by tetraoxoiodate(VII) ion in aqueous acid medium has been studied at 0.03 £ [H+] £ 0.1 mol dm-3 under pseudo-first order conditions of an excess of tetraoxoiodate(VII) concentration at 1 = 0.11 mol dm-3 (NaClO4). The reaction obeys the rate expression: -d [IO4–]/dt = k3K1K2[H+] + k5 [RSH][IO4–] Addition of AcO– and NO3– had no effect on the reaction but the rate of reaction decreased with increase in ionic strength of the medium. Increase in dielectric constant decreased the rate of reaction. The rates are consistent with a mechanism which involves the formation of free radicals which subsequently dimerized into disulfides. The reaction has been rationalized on the basis of the inner-sphere electron transfer mechanism.